Use and Cost Analysis of Comprehensive Respiratory Panel Testing in a Pediatric Emergency Department. Issue 3 (12th March 2023) - Fortenberry, Megan; Zummer, Jaryd; Maul, Erich; Schadler, Aric; Cummins, Megan; Pauw, Emily; Peta, Nihanth; Gardner, Brian
Abstract : Objectives: Fever and respiratory infections are among the leading causes of pediatric emergency department visits and hospitalizations. Although typically self-resolving, clinicians may perform diagnostic tests to determine microbial etiologies of these illnesses. Although comprehensive respiratory viral panels can quickly identify causative organisms, cost to the hospital and patient may be significant. The objective of this study was to analyze the financial impact of comprehensive respiratory viral panel use in relation to associated clinical outcomes. Methods: This study was a single-center, retrospective chart review of pediatric emergency department patients who were evaluated between October 1, 2016, and April 30, 2018, with International Classification of Diseases, Tenth Revision (ICD-10) code diagnoses of acute upper respiratory infection, fever unspecified, and/or bronchiolitis. Our primary outcome was the effect of comprehensive respiratory viral panel testing and results on the total health care charge to patients. Secondary outcomes were the effect of comprehensive respiratory viral panel testing and results on emergency department length of stay and antimicrobial use. Results: A total of 5766 visits were included for primary analysis, with 229 (4%) undergoing comprehensive respiratory viral panel testing. Of these, 163 had a positive result (71%) for at least 1 organism. The total cost was significantly higher in the group that underwent comprehensive respiratory viral panel testing ($643.39 [$534.18–$741.15] vs $295.15 [$249.72–$353.92]; P < 0.001). There was no decrease in emergency department length of stay or significant change in antimicrobial use associated with comprehensive respiratory viral panel use. Conclusions: This study demonstrates that the utilization of comprehensive respiratory viral panels in pediatric emergency department patients with bronchiolitis, unspecified fever, and/or acute upper respiratory infection adds significant cost to patient care without a decrease in their length of stay or antimicrobial use. Further studies are needed to determine the appropriate targeted use of comprehensive respiratory viral panels.